2021
DOI: 10.3389/fimmu.2021.645653
|View full text |Cite
|
Sign up to set email alerts
|

IL-10−/− Enhances DCs Immunity Against Chlamydia psittaci Infection via OX40L/NLRP3 and IDO/Treg Pathways

Abstract: Chlamydia psittaci (C. psittaci) is a common zoonotic agent that affects both poultry and humans. Interleukin 10 (IL-10) is an anti-inflammatory factor produced during chlamydial infection, while dendritic cells (DCs) are powerful antigen-presenting cells that induce a primary immune response in the host. However, IL-10 and DCs regulatory mechanisms in C. psittaci infection remain elusive. In vivo and in vitro investigations of the regulatory mechanisms were performed. IL-10−/− mice, conditional DCs depletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…A persistent inflammatory response can lead to increased lymphocyte apoptosis and immunosuppression. [24][25][26][27][28] In summary, we believe that severe psittacosis pneumonia induces an excessive inflammatory response and immunosuppression in the early stage, and the lymphocyte counts and D-dimer, IL-2, IL-6, and IL-10 levels can help identify the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A persistent inflammatory response can lead to increased lymphocyte apoptosis and immunosuppression. [24][25][26][27][28] In summary, we believe that severe psittacosis pneumonia induces an excessive inflammatory response and immunosuppression in the early stage, and the lymphocyte counts and D-dimer, IL-2, IL-6, and IL-10 levels can help identify the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the IL-10 level of patients with chlamydial infections was higher than that of uninfected individuals (Han et al, 2006 ). In a study on intranasal infection with C. psittaci , IL-10 −/− mice were found to promote activation and assembly of the NLRP3 inflammasome, promoting apoptosis, and leading to chlamydial clearance (Li Q. et al, 2021 ). Studies on mice with IL-10 deletion have shown that the loss of this cytokine distorts the anti-Chlamydial immune response, altering the dominant Th1 phenotype, and preventing Chlamydia -induced immunopathology (Bua et al, 2019 ; Sanchez et al, 2019 ).…”
Section: Non-antibiotic Approachesmentioning
confidence: 99%
“…Upon entering host cells, the EB differentiates into the RB and multiplies within a unique organelle called an inclusion. Furthermore, when RBs differentiate back into EBs, bacteria are released from host cells for transmission 4 . Although C. psittaci is a member of the Chlamydia genus, it has received less attention than other Chlamydia species in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, when RBs differentiate back into EBs, bacteria are released from host cells for transmission. 4 Although C. psittaci is a member of the Chlamydia genus, it has received less attention than other Chlamydia species in previous studies. C. psittaci can lead to respiratory disease in poultry and humans with various clinical signs, which is principally associated with avian chlamydiosis as a continuing risk to the health of humans and poultry.…”
Section: Introductionmentioning
confidence: 99%